2013
DOI: 10.9790/2380-0362327
|View full text |Cite
|
Sign up to set email alerts
|

Blood profile and daily gain of fat-tailed growing rams receiving tree foliages to substitute other ingredients in the concentrate diets

Abstract: This research was aimed to investigate the blood profile and daily gain of fat-tailed growing rams by substituting dried leaves of Moringa oleifera (MOL) and Samanea saman (SSL) to other ingredients in the concentrate feed. 16 growing rams aged between 6 and 8 months (PI 0), average body weight (BW) was 13.83±1.73 kg, were placed randomly in an individual cage. The treatments were P 14 L 0 =14% of CP concentrate feed without leaves supplement, P 14 L M-S =14% of CP concentrate feed with MOL (30%),SSL (10%), P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Supplementation of Moringa oleifera (30%) and Samanea saman (10%) leaves in the concentrate feed (18% crude protein) is given by 1.0% BW on basal diet of maize stover produce average daily gain of 87.7±18.3 g/head/day and normal range blood profile of growing rams. [23]…”
Section: Methane Production In Vitromentioning
confidence: 99%
“…Supplementation of Moringa oleifera (30%) and Samanea saman (10%) leaves in the concentrate feed (18% crude protein) is given by 1.0% BW on basal diet of maize stover produce average daily gain of 87.7±18.3 g/head/day and normal range blood profile of growing rams. [23]…”
Section: Methane Production In Vitromentioning
confidence: 99%
“…In other field experiment Soetanto, Chuzaemi, & Marhaeniyanto (2010) revealed that adding MO in the basal diet of Ettawah goats had 83 % more weight gain that can be attributed to MO supplementation. Other authors reported a 14.5 % increase in daily weight gain of fat-tailed growing rams when MO and Samanea saman leaves were supplemented to a diet containing 18 % crude protein (Marhaeniyanto, Soetanto, Kusmartono, & Hartutik, 2013). Recently, Dahlanuddin, Yanuarianto, Poppi, McLennan, & Quigley (2014) fed male Bali cattle aged between 6 and 12 months with four tree fodder hay as a sole diet, i.e.…”
Section: Introductionmentioning
confidence: 99%